Estrategias creativas y su incidencia en el proceso enseñanza aprendizaje área lengua y literatura a estudiantes de la escuela de educación básica “Isabel Herrera de Velázquez”, cantón Milagro, Provincia Guayas. - Velasco Sánchez, Norma Ebella (2016)
The present research is aimed to be a solution to the difficulties of teaching and learning in the area of Language Arts presented by students of the School of Basic Education "Isabel Herrera de Velázquez", belonging to the canton Milagro, Guayas Province. Many of the students finds it difficult to understand some of the contents of this subject, because of the limited use of creative teaching materials and to encourage the development of basic skills relevant to this area of learning. Originality, creativity and skills of each individual student is a unique skill that is acquired and can be improved, the same as for their development needs prior instruction, this may be using; methodologies teaching techniques, resource or which shall be applied by teachers to help them progress in quality learning, building with suitable professional future to cope every problem. That is why this paper focuses on finding creative strategies for teaching-learning process of students, to advance this research deductive and inductive methods were used to check the creative strategies contribute in the education process.